2022
DOI: 10.52547/ibj.3703
|View full text |Cite
|
Sign up to set email alerts
|

On-Admission Anemia and Survival Rate in COVID-19 Patients

Abstract: Background: Anemia often worsens the severity of respiratory illnesses, and few studies have so far elucidated the impact of anemia on COVID-19 infection. This study aimed to evaluate the effect of anemia at admission on the overall survival of COVID-19 patients using AFT models. Methods: This registry-based, single-center retrospective cohort study was conducted in a university hospital in Ilam, the southwest of Iran, between March 2020 and September 2021. AFT models were applied to set the data of 2,441 COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Interestingly, the prevalence of anemia at admission was similar to the one for community-acquired in both adults 12 and children 27 hospitalised for non-COVID community-acquired pneumonia, thus suggesting that this finding may be a characteristic shared also with other lower-respiratory tract infections. Likewise, the association between baseline presence of anemia and the poor clinical outcomes reported here is consistent with other studies involving patients with both COVID-19 28 , 29 and non-COVID related pneumonia 12 , 27 .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the prevalence of anemia at admission was similar to the one for community-acquired in both adults 12 and children 27 hospitalised for non-COVID community-acquired pneumonia, thus suggesting that this finding may be a characteristic shared also with other lower-respiratory tract infections. Likewise, the association between baseline presence of anemia and the poor clinical outcomes reported here is consistent with other studies involving patients with both COVID-19 28 , 29 and non-COVID related pneumonia 12 , 27 .…”
Section: Discussionsupporting
confidence: 91%
“…A systematic review of 63 studies showed that severe SARS-CoV-2 infection is associated with lower Hb levels [35], and a study by Fan et al showed that 1.6% of SARS-CoV-2 patients admitted to the intensive care unit received blood transfusions for anemia correction [36]. Most studies, including ours, have shown that anemia is an independent predictor of mortality and that each unit of increase in Hb in COVID-19 patients enhanced the survival rate by 4% [30,37,38]. A meta-analysis based on risk factor-adjusted effect estimates indicated that anemia was independently associated with a significantly elevated risk for mortality among COVID-19 patients [39], while another study documented that in COVID-19 patients, anemia is both associated with a more pronounced baseline pro-inflammatory profile and a higher incidence of in-hospital mortality and severe disease [40].…”
Section: Discussionmentioning
confidence: 66%
“…Recent research has demonstrated a link between anemia and severe COVID-19 disease presentation. However, these studies were primarily conducted with adult cohorts or even excluded pediatric populations entirely [ 14 , 15 , 16 ]. However, although it has been shown that children tend to experience a milder course of the disease when compared with adult populations [ 6 ], this case highlights that severe COVID-19 may also occur in pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that iron and B12 deficiencies result in low levels of hemoglobin and red blood cells, leading to a decrease in their oxygen-carrying capacity [ 21 ]. In patients with severe COVID-19 pneumonia, such as the one presented in this case study, this decreased oxygen-carrying capacity is detrimental to patient survival, especially in light of the hyper-metabolic state caused by the infection [ 14 , 15 ]. Moreover, it has been suggested in the literature that SARS-CoV-2 can lower functional hemoglobin levels and interfere with iron transport and red blood cell production, further decreasing oxygen-carrying capacity and exacerbating anemia [ 22 ].…”
Section: Discussionmentioning
confidence: 99%